Home fire - Shamsie, Kamila, 1973- (Bloomsbury Publishing, 2018)
"Ingenious⁵ Builds to one of the most memorable final scenes I've read in a novel this century." ₇The New York Times LONGLISTED FOR THE 2017 MAN BOOKER PRIZE The suspenseful and heartbreaking story of an immigrant family driven to pit love against loyalty, with devastating consequences Isma is free. After years of watching out for her younger siblings in the wake of their mother's death, she's accepted an invitation from a mentor in America that allows her to resume a dream long deferred. But she can't stop worrying about Aneeka, her beautiful, headstrong sister back in London, or their brother, Parvaiz, who's disappeared in pursuit of his own dream, to prove himself to the dark legacy of the jihadist father he never knew. When he resurfaces half a globe away, Isma's worst fears are confirmed. Then Eamonn enters the sisters' lives. Son of a powerful political figure, he has his own birthright to live up to₇or defy. Is he to be a chance at love? The means of Parvaiz's salvation? Suddenly, two families' fates are inextricably, devastatingly entwined, in this searing novel that asks: What sacrifices will we make in the name of love?